Endogenous Glucagon-Like Peptide-1 as a Potential Mediator of the Resolution of Diabetic Kidney Disease following Roux en Y Gastric Bypass: Evidence and Perspectives. (17th September 2014) - Docherty, Neil G.; Le Roux, Carel W.
Abstract : Diabetic kidney disease in patients with type 2 diabetes strongly correlates with the incidence of major cardiovascular events and all-cause mortality. Pharmacological and lifestyle based management focusing on glycaemic, lipid, and blood pressure control is the mainstay of treatment but efficacy remains limited. Roux en Y gastric bypass is an efficacious intervention in diabetes. Emerging evidence also supports a role for bypass as an intervention for early diabetic kidney disease. This paper firstly presents level 1 evidence of the effects of bypass on hyperglycaemia and hypertension and then summarises emerging data on its effects on diabetic kidney disease. Glucagon-like peptide-1 is implicated as a central mediator of diabetes resolution following bypass through the incretin effect. It has been ascribed vasodilatory, pronatriuretic, and antioxidant properties and its exogenous administration or optimisation of its endogenous levels via dipeptidyl peptidase IV inhibition results in antioxidant and antiproteinuric effects in preclinical models of DKD. Some evidence is emerging of translation of coherent effects in the clinical setting. These findings raise the question of whether pharmacotherapy targeted at optimising circulating hormone levels may be capable of recapitulating some of the effects of bypass surgery on renal injury.